Entornos virtuales tridimensionales (3D): alternativa pedagógica para la enseñanza y el aprendizaje de las derivadas - Pimbo Tiban, Ana Gabriel (2024)
Virtual Learning Environments (VLEs) act as an innovative factor in education, facilitating access to a variety of resources that promote motivation, adaptability, interaction, and creativity in the learning process. VLEs have advanced towards the use of 3D virtual environments, which help students understand the real world by representing spaces and objects in 3D. These environments provide new opportunities for learning and solving mathematical exercises and problems. In this context, the objective of this article is to analyze the relationship between three-dimensional virtual spaces and the teaching process of derivatives. The methodology used was a mixed approach, exploratory in nature, descriptive, and correlational analysis. With a quasi-experimental design, the Shapiro-Wilks test was applied to assess the normality of the variable. The study was conducted with 140 participants organized into four groups of 35, using a descriptive-correlational approach. In summary, the use of three-dimensional virtual environments positively impacts the instruction process of derivatives; therefore, it is suggested to adopt these three-dimensional virtual spaces to optimize student assimilation.